Macrozoobenthic community as a bioindicator for the water quality of the Bone River, Gorontalo - Kadim, Miftahul Khair; Pasisingi, Nuralim; Mursalim, Paramita; Arbi, Indah Rianti (Acta Aquatica: Aquatic Sciences Journal, 2024)
The Bone River faces potential pollution due to human activities in the surrounding area. To ensure this, macrozoobenthic is used as a bioindicator, utilizing the characteristics of its constituent communities, which show sedentary behaviour, limited mobility, and sensitivity to water conditions. This research aims to examine the composition of the macrozoobenthic community which reflects the water quality of the Bone River. The research was conducted from May to August 2023 at three observation stations. Water quality evaluation used the Hilsenhoff Family Biotic Index (FBI) methodology. The findings revealed a collection of 1,040 individuals representing 43 macrozoobenthic genera, with Trichoptera, Ephemeroptera, and Diptera widely distributed along the river. A dominance index of 0.2 indicates that there is not a single macrozoobenthic species that dominates, while an FBI value ranging from 3.71 to 5.47 indicates that there is pollution in the Bone River.Keywords: Bioindicator; Family Biotic Index; Macrozoobenthic; River; Water quality